Amitraz toxicity to the midge Chironomus riparius: Life-history and biochemical responses - Monteiro, Hugo R. (2019)
Acute and chronic toxicity of the formamidine pesticide amitraz to the midge Chironomus riparius was assessed using conventional ecotoxicological tests and biochemical approaches (biomarkers). Amitraz is mainly used as an ectoparasiticide in veterinary medicine, but also in agriculture and apiculture. However, information of amitraz toxicity to non-target invertebrates is limited. Besides the impairment of developmental and emergence rates (reduced larval growth, emergence, and delayed development time) caused by chronic exposure to amitraz, acute exposures induced alterations in the antioxidant enzymes glutathione peroxidase (GPx) and catalase (CAT), and in energetic metabolism biomarkers, lactate dehydrogenase (LDH) and electron transport system (ETS) activities. Moreover, lipid peroxidation (LPO) increased by amitraz exposure. Our results reveal potential secondary effects of amitraz to invertebrates and biomarkers that may aid in the interpretation of sub-lethal toxic responses to amitraz. These results add information concerning the potential outcomes of amitraz exposure to freshwater invertebrates underlining the importance of risk assessment studies of formamidine pesticides.